Clinicopathological significance of DNA fragmentation factor 45 and thyroid transcription factor 1 expression in benign and malignant lesions of the gallbladder - Yuan, Yuan; Yang, Zhu-Lin; Zou, Qiong; Cao, Li-Fen; Tan, Xing-Guo; Jiang, Song; Miao, Xiong-Ying (Polish Journal of Pathology, 2013)
Gallbladder cancer (GBC) is one of the most aggressive tumors; we examined the expression level of DNA fragmentation factor 45 (DFF45) and thyroid transcription factor 1 (TTF-1) in benign and malignant lesions of the gallbladder by immunohistochemistry. The results were correlated with clinicopathological features and prognosis. DNA fragmentation factor 45 and TTF-1 expression was significantly higher in gallbladder adenocarcinomas than in the corresponding peritumoral tissues (χ 2 DFF45 = 6.92, χ 2 TTF-1 = 8.68, ps < 0.01), polyps (χ 2 DFF45 = 4.49, χ 2 TTF-1 = 5.35, ps < 0.05), and chronic cholecystitis (χ 2 DFF45 = 12.98, χ 2 TTF-1 = 17.74, ps < 0.01). Negative expression of DFF45 and TTF-1 was significantly associated with tumor differentiation, tumor mass, lymph node metastasis and invasion of adenocarcinomas (p < 0.05). Univariate Kaplan-Meier analysis showed that elevated expression levels of DFF45 and TTF-1 (p < 0.05) were closely associated with increased overall survival. In addition, the average survival time of patients with DFF45(+) TTF-1(+) tumors was significantly higher than those with DFF45(–) TTF-1(–) tumors (p < 0.05). Finally, multivariate Cox regression analysis showed that negative expression of DFF45 and TTF-1 was an independent prognostic predictor in gallbladder adenocarcinoma (p < 0.05). The expression of DFF45 and/or TTF-1 is closely related to the carcinogenesis, progression, clinical behavior and prognosis of gallbladder adenocarcinomas. DNA fragmentation factor 45 and TTF-1 could be progression-associated genes correlating with good prognosis in GBC.